Forebrain mechanisms of pain modulation - Bushnell, M. Catherine (Henry Stewart Talks, 2009)
Involvement of the forebrain in pain perception, Descending pain control pathways from cortex, Attentional modulation of pain, Emotional modulation of pain, Empathy and pain, Placebo analgesia, Role of forebrain opiates and dopamine in analgesia